Study on Phonon Anharmonicity in a Framework Material H\({_3}\)[Co(CN)\({_6}\)] - Mishra, K. K. (New Innovations in Chemistry and Biochemistry Vol. 4, 2021)
Since last several years, the author has been studying the phonons on functional materials and has established structure-property correlations on flexible framework structure materials, lead free oxides, thin film perovskites, low dimensional 2D materials like graphene nanosheets, TiS3 nanofiber, VSe2 nanosheets, SnO2 quasi nanoparticles etc. In this book chapter, temperature dependent Raman spectroscopic studies on negative thermal expansion framework material H3[Co(CN)6] have been presented in the temperature range 80-300 K to elucidate the phonon anharmonicity of different phonons. No discontinuous or slope changes of phonon mode frequencies, linewidths and their band intensities were noticed suggesting that the compound was stable in the entire temperature range of investigation. Phonon anharmonicity models were used to analyse the temperature dependencies of mode frequencies and their linewidths. It was observed that the three-phonon decay process was dominant over the four-phonon process in this flexible compound. Concisely, the present study demonstrates the anharmonicity of the phonons and their correlation on thermal expansion of H3[Co(CN)6] framework material.